Comparison of the Effects of Treadmill Trainings on Walking and Balance Functions by Increasing the Speed and Incline in Chronic Patients with Stroke - Alipsatici, Cagri; Alaca, Nuray; Canbora, Mehmet Kerem (GALENOS PUBL HOUSE, 2020)
Objective: Improvement of walking is an important goal in stroke rehabilitation. This aim of this study was to compare the effects of treadmill training on walking and balance functions by increasing the speed or incline in patients with chronic stroke. Materials and Methods: Twenty-eight patients with chronic stroke who had symptoms of motor function plateau, were included in the study. Patients were divided into two groups: conventional treatment and treadmill training with increased speed {[}group (CTIS)

n=14] and conventional treatment and treadmill training with increased incline {[}group (CTII)

n=14]. The rehabilitation program was conducted three times per week for eight weeks. The following tests were performed before and after treatment: six-minute walking test (6MWT), ten-meter walking test (10MWT), Berg Balance scale, Beck Depression inventory, stride length, and cadence assessments. Results: In the pre- and post-treatment evaluations of both groups, walking and balance function and depression scale scores improved statistically (p<0.001). The between-group comparisons demonstrated that the CTIS group had a statistically significant improvement in the evaluation of 6MWT (p=0.023), 10MWT (p=0.006), stride length (p=0.004), and cadence (p<0.001) compared with the CTII group. Conclusion: Together, our data demonstrate that walking training on a treadmill has positive results on walking and balance functions, as well as the emotional levels of patients with chronic stroke in the assumed plateau period. We anticipate that treadmill walking training performed with increased speed may be more beneficial than increasing the incline in patients with stroke.
Keywords: Stroke; plateau; treadmill; incline; speed